Metabolic regulation of mitochondrial рH gradient and oxidative stress in rat brain synaptosomes - Hrynevich, Svetlana V.; Fedorovich, Sergey V. (Experimental Biology and Biotechnology, 2025)
Metabolic changes may affect different transmembrane potentials of synaptic mitochondria and antioxidant cell defence systems. The influence of processes such as the glucose withdrawing from the incubation medium and its replacing with the ketone body β-hydroxybutyrate (BHB) at a concentration of 8 mmol/L on mitochondrial pH gradient, the formation of free radicals and the reduced glutathione level in rat brain synaptosomes was studied. It was established that replacing glucose with BHB in the incubation medium leads to an enhancement of mitochondrial uptake of the acridine orange fluorescent probe that reflect an increase in the mitochondrial pH gradient. At the same time, this effect did not affect the fluorescence level of the 2′,7′-dichlorodihydrofluorescein diacetate probe that indicate no changes in the formation of free radicals. Also BHB was ineffective as an antioxidant against oxidative stress induced by the addition to the incubation medium of 1 mmol/L hydrogen peroxide or extracellular acidification to the pH level of 6.0. Complete withdrawing of glucose from the incubation medium caused a small but statistically significant increase of reduced glutathione pool. The pentose phosphate pathway inhibitor 6-aminonicotinamide (1 mmol/L) caused a paradoxical increase of reduced glutathione content. It was concluded that changes in the metabolic status of synaptosomes can affect the synaptic mitochondrial pH gradient and the reduced glutathione level.
Keywords: synapse; synaptosome; mitochondrion; free radical; ketogenic diet; hypoglycemia